Precopulatory Sexual Cannibalism and Other Accidents: Evolution, Material Trans Theory, and Natural Law. Issue 1 (2nd January 2018) - Schaefer, Donovan
ABSTRACT: Natural law perspectives take existing formations of life-matter and translate them into normative templates. From an evolutionary perspective, the normative aspect of natural law is always under suspicion. Because life-forms have histories and futures that are shaped by a dynamic of accidents, they are not susceptible to normative assertions about what they "should" be or do. This is particularly the case with sex. Sexual reproduction is a minoritarian strategy within the full spectrum of life. Like all aspects of life, sex is a product of a fluctuating backdrop of phylogenetic (species-forming) and ontogenetic (individual-forming) accidents. And like all aspects of life, it continues to vary within this field of material processes. My argument in this essay is that, rather than a fully integrated feature of a lawlike apparatus, sex is a mess. From the evolutionary perspective—and especially, I show, in the light of the new "extended evolutionary synthesis"—sex always has been and always will be barnacled with accidents. This dovetails with what we might call material trans theory, a species of New Materialism that sees sex as a concrescence of material forces and processes introjected into bodies. Both views leave sex fundamentally incompatible with metaphysical explanations or metaphysical norms—including and especially natural law.